2013
DOI: 10.1063/1.4823780
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the accuracy of noise measurements by the two-amplifier correlation method

Abstract: We present a novel method for device noise measurement, based on a two-channel cross-correlation technique and a direct "in situ" measurement of the transimpedance of the device under test (DUT), which allows improved accuracy with respect to what is available in the literature, in particular when the DUT is a nonlinear device. Detailed analytical expressions for the total residual noise are derived, and an experimental investigation of the increased accuracy provided by the method is performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In most digital signal analyzers, an internal programmable signal source (V s ) with a white spectrum is available, which allows the direct measurement of H 1 and H 2 . As can be seen from the expressions for the K Ii and K V i coefficients determined in [3], the K Ii terms are much smaller than unity, while the K V i are of the order of 1/R 2 d . Thus the contributions from the current noise sources are strongly suppressed, while those from the voltage noise sources are substantially the same as without cross-correlation.…”
Section: Series Configurationmentioning
confidence: 93%
See 4 more Smart Citations
“…In most digital signal analyzers, an internal programmable signal source (V s ) with a white spectrum is available, which allows the direct measurement of H 1 and H 2 . As can be seen from the expressions for the K Ii and K V i coefficients determined in [3], the K Ii terms are much smaller than unity, while the K V i are of the order of 1/R 2 d . Thus the contributions from the current noise sources are strongly suppressed, while those from the voltage noise sources are substantially the same as without cross-correlation.…”
Section: Series Configurationmentioning
confidence: 93%
“…In a recent paper [3] we have shown that the equivalent cross-spectrum S I12 at the DUT can be expressed as…”
Section: Series Configurationmentioning
confidence: 99%
See 3 more Smart Citations